Patient Factors Predicting Weight Loss after Roux-en-Y Gastric Bypass - Linda Sillén; Ellen Andersson (Journal of Obesity)
Objective. The purpose of this study was to identify preoperative factors predicting weight loss following Roux-en-Y gastric bypass (RYGB) surgery. Material and Methods. 281 patients subjected to RYGB between January 2006 and June 2012 were included. Demographic, physical, and socioeconomic factors were assessed with regression analysis. Dependent variable was percent of excess weight loss (% EWL) at follow-up. Results. Follow-up data at one year was available in 96%, at two years in 88%, and at three years in 65% of the patients. Mean EWL was 72.5%. The success rate (defined as ≥60% EWL) at 1 year was 73% and at 2 years 74% and was 71% after 3 years. An earlier onset of obesity and high preoperative BMI were independently associated with unsuccessful weight loss at 1-year follow-up. At 2-year follow-up, an association between unsuccessful weight loss and psychiatric disorder, diabetes, hypertension, and preoperative BMI was seen. At 3-year follow-up no statistically significant associations were detected. Conclusions. RYGB provides successful weight loss for most patients. The results from this study indicate that an earlier age of onset of obesity, high preoperative BMI, psychiatric disorder, diabetes, and hypertension are associated with unsuccessful weight loss.